Antimicrobial susceptibility of Staphylococci isolated from bovine mastitis at "Zona da Mata"- MG, Brazil - Ferreiro, Laerte; Melo, Mauro Teixeira de (Pesquisa Agropecuaria Brasileira, 2014)
Three hundred and fifty-four antibiograms were performed with 300 strains of Staphylococcus aureus and 54 of S. epidermidis using the diffusion method. Among the S. aureus, 165 (55%) were completely susceptible to the eleven antimicrobial agents tested; -67 (22,3%) resistants to penicillin G (PEN), 5 (1,7%) to tetracycline (TET), 4 (1,3%) to chloramphenicol (CLR), 2 (0,6%) to streptomycin and 2 (0,6%) to lincomycin in vitro. Multiple resistance was found in about 15% of the isolates, being most common the combinations involving PEN: STR: TET and CLR. According to the source of staphylococcal infection, 259 (86,3%) were strains of bovine origin, 29 (9,7%) human and 12(4%) canine, being the bovine ones much more resistant except to novobiocin, cloxacillin and rifamycin. Regarding the 54 S. epidermidis, 28 (51,8%) showed total susceptibility and 16 (29,6%) multiple resistance, specially combinations of PEN: STR: TET: CLR and Sulfisoxazole (SUL). All 354 strains were susceptible to rifamycin (rifampim).